Changes in car and bus usage amid the COVID-19 pandemic: Relationship with land use and land price. (October 2021) - Kim, Suji; Lee, Sujin; Ko, Eunjeong; Jang, Kitae; Yeo, Jiho
Abstract: This study aimed to explore the impacts of COVID-19 on car and bus usage and their relationships with land use and land price. Large-scale trip data of car and bus usage in Daejeon, South Korea, were tested. We made a trip-chain-level data set to analyze travel behavior based on activity-based travel volumes. Hexagonal cells were used to capture geographical explanatory variables, and a mixed-effect regression model was adopted to determine the impacts of COVID-19. The modeling outcomes demonstrated behavioral differences associated with using cars and buses amid the pandemic. People responded to the pandemic by reducing their trips more intensively during the daytime and weekends. Moreover, they avoided crowded or shared spaces by reducing bus trips and trips toward commercial areas. In terms of social equity, trips of people living in wealthier areas decreased more than those of people living in lower-priced areas, especially trips by buses. The findings contribute to the previous literature by adding a fundamental reference for the different impacts of pandemics on two universal transportation modes. Highlights: The usage behaviors of cars and buses were different amid the COVID-19 pandemic. Car and bus usage diminished more during the daytime and weekends. People responded to pandemic by avoiding taking buses and going to crowded areas. People living in wealthier neighborhoods reduced their trips more than others during the pandemic. People living in wealthier neighborhoods were more reluctant to use buses than cars.